Optimizing the superstructure configuration of highway bridges for cost-effective construction - Dina M. Mansour; Ahmed M. Ebid; Ibrahim M. Mahdi; Hisham A. Mahdi; Anwar F. Elkadi (Heliyon, 2024)
The structural progress of bridges in conjunction with efficiency has gained researchers’ attention in the last few decades. Structures optimization applying mathematical analysis is utilized to achieve sustainability in the design and construction of bridges. Despite the extensive research in this area of knowledge, further structural optimization development needs to be developed.The main goal of this research is to develop a decision support system (DSS) that selects the optimum superstructure configuration for highway bridges, considering financial and technical parameters. The most common structural systems in the longitudinal and transverse directions of bridges are considered in this research. Simple and continuous spans are included in the longitudinal direction, while open and closed sections for the transverse direction. Different construction materials are considered as well, like reinforced concrete, pre-stressed concrete, steel sections, and composite sections, to achieve a wide diversity of alternatives. The developed DSS was illustrated graphically as a map for the optimum superstructure configuration for certain span and span to depth ratio combinations. These different configurations obtained from the DSS were mapped three times. The first was based on direct cost only, the second on construction time only, and the third on the total cost of each alternative. Eventually, the DSS was verified using collected case studies and proposed a convenient selection of bridge superstructure configurations within the considered range of span dimensions.